Sputum versus bronchial washings for diagnosis of pulmonary tuberculosis- a prospective study of 53 patients - Patel, Dharmeshkumar; Kamdar, Deepali J. (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is a major global public health problem. It is caused by mycobacterium tuberculosis and it is a leading cause of death in developing countries like India. WHO recommends the detection of acid fast bacilli in sputum as the initial diagnosis of pulmonary TB. Tuberculosis is spread from person to person through air by droplet nuclei. So, early detection and prompt treatment of tuberculosis is main cornerstone to prevent transmission into community. Bronchial washing is very helpful for early detection of mycobacterium tuberculosis. Methods: This is a prospective study of 53 sputum smear negative patients underwent for bronchoscopy. After a detailed medical history and physical examination, Patients with a negative sputum smear AFB examination and a strong clinco-radiological suspicion of pulmonary tuberculosis were then counseled, consented and subjected to fiber-optic bronchoscopy with bronchial washings and bronchial biopsy in case of endobronchial lesions. Results: Our study showed mean age of patient is about 43.49 year and has predominantly male patients. Most cardinal symptoms were fever (83%) and cough (74%). Most radiological findings were consolidation and cavity lesion accordingly. Sputum culture was positive in 14 (26%) patients out of 53 patients and bronchial washing smear positive for AFB in 30 (57%) patients and bronchial washing culture positive for AFB in 40 (75%) patients out of 53 patients. Conclusions: Bronchial washings analysis for detection of AFB is much more reliable in comparison to direct smear microscopy and direct sputum culture examination.